Effectiveness of Brain Gym Activities in Enhancing Writing Performance of Grade I Pupils - Ocampo, Jr., Jose M; Varela, Leonora P; Ocampo, Laura V (SOSIOHUMANIKA, 2017)
ABSTRACT: There are many factors that influence academic performance of students. Some of these are related to personological, sociological, and psychological factors. In recent years, academic achievement and performance have been linked to several psychological factors. Two of these psychological factors, that may have direct impact or influence to academic performance, are curiosity and epistemological beliefs. In this study, the organization and legibility of the subjectsâ writing before and after the use of Brain Gym activities were described. The pre-experimental design, specifically the One Group Pre-test â Post-test, was utilized to examine the grade 1 pupilsâ writing performance in the areas of length of output. The respondents were composed of 4 pupils, who have a variety of writing concerns, ranging from getting started, organization, attention to details, and producing sufficient output or length of writing. It was concluded that Brain Gym, a movement-based learning exercise, was an effective activity for enhancing grade 1 pupilsâ writing concerns, specifically in terms of neatness, legibility, writing on and following blue-red-blue lines as well as correct spacing between letters and words. Pupils under the Brain Gym conditions tended to write more words. Brain Gym exercises brought excitement, cheerfulness, and relaxed mood among pupils. It is recommended that time be allotted for the use of Brain Gym exercises, due to it can be utilized as unfreezing activity for enhancement of writing performance among pupils.KEY WORD: Brain Gym; Writing Performance; Legibility; Length of Output; Organization; Writing Concerns.Â RESUME: âEfektivitas Kegiatan Senam Otak dalam Meningkatkan Kinerja Menulis Siswa Kelas Iâ. Ada banyak faktor yang mempengaruhi prestasi akademik siswa. Beberapa di antaranya berkaitan dengan faktor personologis, sosiologis, dan psikologis. Dalam beberapa tahun terakhir, prestasi dan kinerja akademik telah dikaitkan dengan beberapa faktor psikologis. Dua faktor psikologis ini, yang mungkin berdampak langsung atau berpengaruh pada kinerja akademis, adalah keingintahuan dan kepercayaan epistemologis. Dalam penelitian ini, organisasi dan keterbacaan tulisan subjek sebelum dan sesudah penggunaan kegiatan Senam Otak dijelaskan. Desain pra-eksperimental, khususnya Pre-test â Post-tes Satu Grup, digunakan untuk menguji kinerja tulis murid kelas 1 di bidang panjang dan luaran. Responden terdiri dari 4 siswa, yang memiliki berbagai masalah menulis, mulai dari persiapan, pengorganisasian, perhatian terhadap perincian, dan menghasilkan luaran atau lama penulisan yang cukup. Disimpulkan bahwa Senam Otak, sebuah gerakan berbasis pembelajaran, adalah kegiatan yang efektif untuk meningkatkan perhatian siswa kelas 1, khususnya dalam hal kerapian, keterbacaan, penulisan dan garis biru-merah-biru berurutan, dan jarak antara huruf dan kata yang benar. Siswa di bawah kondisi Senam Otak cenderung untuk menulis lebih banyak kata. Latihan Senam Otak membawa kegembiraan, keceriaan, dan suasana santai di kalangan siswa. Dianjurkan agar waktu diberikan untuk penggunaan latihan Senam Otak ini, sebab ianya dapat dimanfaatkan sebagai aktivitas tanpa henti untuk meningkatkan kinerja menulis di kalangan siswa.KATA KUNCI: Senam Otak; Kinerja Menulis; Keterbacaan; Panjang Luaran; Organisasi; Perihal Menulis.Â Â Â Â About the Authors: Jose M. Ocampo, Jr., Ph.D.Â is a Full Professor at the Faculty of Education Sciences PNU (Philippine Normal University) in Manila, Philippines. Leonora P. Varela, Ph.D. is an Associate Professor at the Faculty of Education Sciences PNU in Manila, Philippines. Laura V. Ocampo, M.A. is a Science Grade School Teacher at the Claret School, Quezon City, Philippines. Corresponding authors are: juno_6970@yahoo.com, varela.lp@pnu.edu.ph, and hope4619@gmail.comSuggested Citation: Ocampo, Jr., Jose M., Leonora P. Varela & Laura V. Ocampo. (2017). âEffectiveness of Brain Gym Activities in Enhancing Writing Performance of Grade I Pupilsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Volume 10(2), November, pp.179-190. Bandung, Indonesia: Minda Masagi Press and UNIPA Surabaya, ISSN 1979-0112. Article Timeline: Accepted (September 29, 2017); Revised (October 30, 2017); and Published (November 30, 2017).